Association of moderate chronic kidney disease with insufficient improvement of fractional flow reserve after stent implantation. Issue 2 (22nd October 2015) - Sakoda, Kunihiro; Tanaka, Nobuhiro; Hokama, Yohei; Hoshino, Kou; Murata, Naotaka; Yamashita, Jun; Yamashina, Akira
Abstract : Objectives: This study aims to investigate the association of moderate chronic kidney disease (CKD) with fractional flow reserve (FFR) after stent implantation. Background: Patients with moderate CKD have a higher prevalence of severe and diffuse coronary artery disease, and have increased risk of cardiovascular events even after stent implantation. On the other hand, in some patients, FFR could not be sufficiently improved even after stent implantation. However, the association between these pathophysiological processes is unclear. Methods and Results: A total of 102 patients with stable angina, in whom a stent was implanted for the left anterior descending coronary artery (LAD) lesion, were included. Patients with a severely decreased glomerular filtration rate (GFR; > CKD stage 4) were excluded. Patients were stratified into 3 groups: those with an estimated GFR (eGFR) ≥ 60 mL per min per 1.73 m 2 (stage 0‐2), 45 to 59 mL per min per 1.73 m 2 (stage 3a), and 30 to 44 mL per min per 1.73 m 2 (stage 3b). FFR after stent implantation (post‐stent FFR) was significantly lower in the stage 3b group than in both the stage 0‐2 group and the stage 3a group ( P < 0.01). Post‐stent FFR had a significant positive correlation with eGFR ( r = 0.223, P = 0.024). Multivariate analysis demonstrated that eGFR was an independent predictor of post‐stent FFR. Conclusions: Moderate CKD was independently associated with insufficient improvement of FFR after stent implantation. This can partly explain the poor prognosis of patients with CKD. © 2015 Wiley Periodicals, Inc.